TEST LEVELS OF LYCOPENE AND ANTIOXIDANT ACTIVITY IN NATURALLY FERMENTED TOMATO (LYCOPERSICON ESCULENTUM) - Anggraeni In Oktavia; Bella Septiana Adinda Sari; Vellanie Vira Savitrie (Jurnal Pangan dan Agroindustri, 2022)
The natural fermentation method for tomatoes is an alternative to avoid rotting tomatoes and increase their selling value. Fermentation is also able to increase the  secondary metabolites. Tomatoes contain lycopene as an antioxidant. The aim of the study was to calculate lycopene levels and antioxidant activity in naturally fermented tomatoes. Research method: total lycopene levels were measured using a UV-Vis 472 nm spectrophotometer. Antioxidant levels were measured using the DPPH method (1,1-Diphenyl-2-Picryl Hydrazil). The results showed that the lycopene content of fresh tomatoes was 0.05149mg/100mL while naturally fermented tomatoes were 0.1254 mg/100mL. Antioxidant levels in fresh tomatoes were based on the IC50 value, which was 57.93 mg/L, while the IC50 for fermented tomatoes was 45.82 mg. /L. The conclusion of this study was the levels of lycopene in naturally fermented tomatoes were higher and the levels of antioxidants in naturally fermented tomatoes were higher than in fresh tomatoes.